2019
DOI: 10.5371/hp.2019.31.2.63
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Bipolar Hemiarthroplasty versus Total Hip Arthroplasty: Assessing the Potential Impact of Cement Use and Pre-Injury Activity Levels in Elderly Patients with Femoral Neck Fractures

Abstract: Purpose This study was performed to analyze the potential impact of cement use and favorable pre-injury activity on clinical outcomes of bipolar hemiarthroplasty (BHA) compared with total hip arthroplasty (THA) in elderly patients with femoral neck fractures. Materials and Methods Systematic review and meta-analysis of 12 clinical studies (5 randomized controlled trials and 7 comparative studies). Subgroup analysis was performed based on type of fixation method (cemente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…For EQ-5D scores, our conclusion agreed with other studies that THA has better overall patients' quality of life ([24]; Y [28,48,49].). We did the subgroup analysis and found that the difference became obvious 2 years after the surgery.…”
Section: Patients' Quality Of Lifesupporting
confidence: 91%
See 3 more Smart Citations
“…For EQ-5D scores, our conclusion agreed with other studies that THA has better overall patients' quality of life ([24]; Y [28,48,49].). We did the subgroup analysis and found that the difference became obvious 2 years after the surgery.…”
Section: Patients' Quality Of Lifesupporting
confidence: 91%
“…Hospital and surgery outcomes For surgery time, almost all previous synthesized outcomes are in consistence with our results [24,28,33,48,49]. And we consider the main reasons are that HA requires less operative installation steps including cup preparation and implantation.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Unlike unipolar hemiarthroplasty, BHA is designed to provide the inner bearing between the femoral head and the polyethylene surface and the outer bearing between the acetabular cup and the acetabulum [2][3][4] . Compared with THA, BHA is more frequently performed type of arthroplasty because this procedure is a less complicated surgery without acetabular replacement and has the advantage of an increased jumping distance that lowers the risk for dislocation 5) . Like in THA, the FO is important in BHA.…”
Section: Discussionmentioning
confidence: 99%